Parents' experiences and satisfaction with care during the birth of their very preterm baby: a qualitative study - Sawyer, A.; Rabe, H.; Abbott, J.; Gyte, G.; Duley, Lelia; Ayers, S. (Wiley, 2013)
Objective: To assess parents' experiences and satisfaction with care during very preterm birth and to identify domains associated with positive and negative experiences of care.